Emergence and dissemination of three mild outbreaks of Neisseria gonorrhoeae with high-level resistance to azithromycin in Barcelona, 2016–18. (26th December 2020) - Salmerón, P; Moreno-Mingorance, A; Trejo, J; Amado, R; Viñado, B; Cornejo-Sanchez, T; Alberny, M; Barbera, M J; Arando, M; Pumarola, T; Hoyos-Mallecot, Y; Serra-Pladevall, J; et al.
Abstract: Background: Neisseria gonorrhoeae (NG) isolates with high-level azithromycin resistance (HL-AziR) have emerged worldwide in recent decades, threatening the sustainability of current dual-antimicrobial therapy. Objectives: This study aimed to characterize the first 16 NG isolates with HL-AziR in Barcelona between 2016 and 2018. Methods: WGS was used to identify the mechanisms of antimicrobial resistance, to establish the MLST ST, NG multiantigen sequence typing (NG-MAST) ST and NG sequence typing for antimicrobial resistance (NG-STAR) ST and to identify the clonal relatedness of the isolates with other closely related NG previously described in other countries based on a whole-genome SNP analysis approach. The sociodemographic characteristics of the patients included in the study were collected by comprehensive review of their medical records. Results: Twelve out of 16 HL-AziR isolates belonged to the MLST ST7823/NG-MAST ST5309 genotype and 4 to MLST ST9363/NG-MAST ST3935. All presented the A2059G mutation in all four alleles of the 23S rRNA gene. MLST ST7823/NG-MAST ST5309 isolates were only identified in men who have sex with women and MLST ST9363/NG-MAST ST3935 were found in MSM. Phylogenomic analysis revealed the presence of three transmission clusters of three different NG strains independently associated with sexual behaviour. Conclusions: Our findings support the first appearance of three mild outbreaks of NG with HL-AziR in Spain. These results highlight the continuous capacity of NG to develop antimicrobial resistance and spread among sexual networks. The enhanced resolution of WGS provides valuable information for outbreak investigation, complementing the implementation of public health measures focused on the prevention and dissemination of MDR NG.